Perbedaan Titer Imunoglobulin G Anti Campak Bayi Baru lahir Aterm dengan Preterm di RSUD Dr.Moewardi Surakarta - Subagyo, Bambang; Hafidh, Yulidar; Wahyu Herlinawati, Sri (Majalah Kesehatan Pharmamedika, 2011)
Infants are protected from infections due to maternal IgG which were taken intrauterine. Gestational age is predicted to have direct correlation with IgG titer in newborn. The aim of this study was to find out the mean difference of anti measles IgG titer between preterm and aterm newborn. Preterm newborns were taken consecutively and appropriated by gender to aterm groups. Laboratory examination and interview to the parents were performed. Paired t-test were used to compare anti measles IgG titer between two groups. Multivariate analysis were performed to factors contributed in anti measles IgG titer. The result showed the mean difference was significant, between anti measles IgG titer preterm and aterm newborn. The mean difference was 1417,05 mIU/ml (p0,05). The mean of anti measles IgG titer was lower in preterm newborn compared with aterm. Multivariat analysis showed prematurity is risk factor for a low level anti measles IgG titer in newborn. This study concluded that the mean of anti measles IgG titer in preterm newborn is lower than aterm. Prematurity is risk factor for a low level anti measles IgG titer in newborn. Maternal anti measles IgG and uteroplacenta circulation give contribution to anti measles IgG titer in newborn.